Validação clínica de checklist para transfusão sanguínea em crianças - Bezerra, Carolina Martins (2023)
Blood transfusion is a therapy for some clinical conditions, transplants, chemotherapies and surgeries. Understanding the complexity of the transfusion act in children performed by the nurse, the use of technologies, such as the checklist, which combine scientific knowledge and care practice provide a more qualified and efficient care, thus avoiding errors resulting from lapses or slips, if necessary. The objective was to validate the Checklist for blood transfusion in children in clinical practice. Psychometric study, carried out from August 2021 to November 2022, in a public hospital of reference in pediatrics in Fortaleza - CE. Developed in three stages: online training for three nurses to qualify the transfusion act; interobserver reliability with the evaluation of 70 transfusions and the application of the checklist in clinical practice in 140 transfusions. Descriptive statistics, reliability using the kappa coefficient, exploratory and confirmatory factor analysis, Cronbach's Alpha and McDonald's Omega were performed. Participants signed the Free and Informed Consent Form according to Resolution nº466/12. Study approved with opinion numbers 4.663.872 and 4.840.749. The results showed a global kappa of 0.86, in clinical validation, the Checklist for blood transfusion in children - version 2 was applied by nurses aged 37 to 42 years, graduated from one to five years, specialists in Oncology Nursing and who did not participate in hemotherapy training. Blood transfusions were intended for children aged 6 to 10 years with oncohematological diseases, with platelet concentrate being the most infused blood component. In the factorial analysis, of the 64 items in version 2 of the checklist, 20 items were excluded, later, another 18 were indicated for exclusion, originating version 3 with 26 items. The second analysis showed good adequacy of the sample with values of KMO=0.66 and TBS with p=0.001. Factor loadings ranged from 0.763 to 0.896 and commonalities from 0.188 to 0.899. From the Checklist for blood transfusion - version 3, six items did not show significant factorial results in the analyses but were maintained due to their relevance to transfusion safety. Checklist version 4 presented a five-dimensional model with a general Cronbach's Alpha of 0.73 and McDonald's Omega of 0.71. The instrument was called “Checklist for transfusion safety in children” with 32 items. It was concluded that the instrument is a valid, reliable and reliable health technology for the provision of Nursing care in the transfusion act in children. The validated technology will allow nurses to administer blood transfusions with standardized actions for transfusion safety.